The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/cancers13194756
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Therapies for Immunogenic Cell Death and Related Molecules to Potentially Cure Primary Breast Cancer

Abstract: How primary breast cancer can be cured after (neo)adjuvant therapy remains unclear at the molecular level. Immune activation by anticancer agents may contribute to residual tumor cell eradication with postsurgical (neo)adjuvant chemotherapy. Chemotherapy-induced immunogenic cell death (ICD) may result in long-term immune activation with memory effector T cells, leading to a primary breast cancer cure. Anthracycline and taxane treatments cause ICD and immunogenic modulations, resulting in the activation of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 135 publications
0
12
1
Order By: Relevance
“…Since IL-2/JES6 highly selectively stimulates IL-2Rα + cells, represented mostly by Tregs in naïve unprimed mice, it was considered as an immunotherapeutic tool for the specific expansion of Tregs in vivo with a potential application in the treatment of autoimmune diseases and pre-transplantation care. On the contrary, our data showed that it promotes anti-tumor response of CD8 + T cells, particularly in the combination with immunogenic chemotherapy [23], and that this anti-tumor activity was not counteracted by Tregs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since IL-2/JES6 highly selectively stimulates IL-2Rα + cells, represented mostly by Tregs in naïve unprimed mice, it was considered as an immunotherapeutic tool for the specific expansion of Tregs in vivo with a potential application in the treatment of autoimmune diseases and pre-transplantation care. On the contrary, our data showed that it promotes anti-tumor response of CD8 + T cells, particularly in the combination with immunogenic chemotherapy [23], and that this anti-tumor activity was not counteracted by Tregs.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, we found increased frequencies of KILR cells in the spleens and tumors in mice with cancer treated with Dox and IL-2ic. The antigenic stimulation was probably provided by tumor-associated antigens released from cancer cells undergoing the immunogenic cell death induced by Dox [24, 25]. The expression of IL-7Rα in KILR effector CD8 + T cells is striking as conventional effector T cells are characterized as IL-7Rα - , which is associated with their short lifespan [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“… 33 , 34 , 35 Immunogenic cell death and immunogenic modulation by adjuvant chemotherapy may also explain the eradication of residual tumor cells after surgical treatment, resulting in the curing of the primary breast cancer, in responders. 36 The immunomodulatory effects of anticancer drugs have been reported not only for anthracyclines and taxanes, but also for oral fluoropyrimidines such as capecitabine. 37 , 38 , 39 Thus, successful immune activation by anticancer agents may eradicate residual tumor cells after surgical treatment and lead to a cure, but which factors are need for such activation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These NAC‐induced immune activations are thought to involve immunogenic cell death by anthracyclines and immunogenic modulation by taxanes, which can reactivate antitumor immunity by modulating tumor‐infiltrating lymphocytes in the immunosuppressive tumor microenvironment 33–35 . Immunogenic cell death and immunogenic modulation by adjuvant chemotherapy may also explain the eradication of residual tumor cells after surgical treatment, resulting in the curing of the primary breast cancer, in responders 36 . The immunomodulatory effects of anticancer drugs have been reported not only for anthracyclines and taxanes, but also for oral fluoropyrimidines such as capecitabine 37–39 .…”
Section: Discussionmentioning
confidence: 99%
“…Photodynamic therapy (PDT), which use the reactive oxygen species (ROS) produced from the molecular oxygen in the presence of photosensitizers and suitable excitation lights, is recently emerged as complementary and unconventional oncology treatment and may be a suitable palliative treatment option as it is a minimally invasive procedure 5 - 8 . ROS produced in the process of PDT can cause apoptosis of tumor cells 9 , accompanied by the release of damage-associated molecular patterns (DAMPs) including adenosine triphosphate (ATP) or calreticulin (CRT), and high mobility group box 1 (HMGB1) from dying tumor cells 10 - 13 . These DAMPs then cause the maturation of DCs and the activation of effector T cells, increasing the host antitumor immune response 14 - 18 .…”
Section: Introductionmentioning
confidence: 99%